Investigation of Lower Limb Fatigue on Two Standing Posture - Sari Julia Sartika; Siti Zawiah Dawal (Jurnal Optimasi Sistem Industri, 2012)
The purpose of this study was to investigate the different effect from the two standing posture on lower limb fatigue and discomfort. Sixteen subjects (eight females and eight males), aged between 23-29 years, participated in the experiment. They performed a sorting task in front of a grading table by picking and placing objects for 90 minutes in two posture (1) standing and (2) standing using a footrest. Muscle activity was recorded with surface EMG through disposable electrodes. The result shows that standing for ninety minutes developed fatigue in lower limb muscles and back muscles that lead to low back pain. Standing using a footrest result proper posture for prolonged standing period and reduce force at the back. It also results less fatigue and reduce the %MVC of EMG. So, it is recommended to attach a footrest in standing workstation to reduce the fatigue and discomfort.